Evaluate ∫ 0 ∞ e x − 1 x 3 d x .
Give your answer to 2 decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Used the same method !!!
Wonderful , learned a new thing
First we prove the following proposition:
Proposition :
∫ 0 1 x a ln k x d x = ( a + 1 ) k + 1 ( − 1 ) k k ! for k = 0 , 1 , 2 , …
Proof :
Note that ∫ 0 1 x a d x = a + 1 1 for α > − 1 . Differentiating equation above k times w.r.t. a we have ∫ 0 1 ∂ a k ∂ k ( x a ) d x = ∫ 0 1 x a ln k x d x = ( a + 1 ) k + 1 ( − 1 ) k k ! Q.E.D.
Now, we will evaluate the general case of
∫ 0 ∞ e b x − 1 x a − 1 d x = ∫ 0 ∞ 1 − e − b x x a − 1 e − b x d x for a , b > 0
Set y = e − b x , then
∫ 0 ∞ e b x − 1 x a − 1 d x = b a ( − 1 ) a − 1 ∫ 0 1 1 − y ln a − 1 y d y
Use a geometric series for 1 − y 1 then interchange the integral and summation sign which is justified by the Fubini–Tonelli theorem and apply the previous proposition, we have
∫ 0 ∞ e b x − 1 x a − 1 d x = b a ( − 1 ) a − 1 ∫ 0 1 k = 0 ∑ ∞ y k ln a − 1 y d y = b a ( − 1 ) a − 1 k = 0 ∑ ∞ ∫ 0 1 y k ln a − 1 y d y = b a ( − 1 ) a − 1 k = 0 ∑ ∞ ( k + 1 ) a ( − 1 ) a − 1 ( a − 1 ) ! = b a ( a − 1 ) ! k = 1 ∑ ∞ k a 1 = b a Γ ( a ) ζ ( a )
where Γ ( a ) is the gamma function and ζ ( a ) is the Riemann zeta function .
Hence, by setting a = 4 and b = 1 , we have
∫ 0 ∞ e x − 1 x 3 d x = Γ ( 4 ) ζ ( 4 ) = 3 ! ⋅ 9 0 π 4 = 1 5 π 4
Well this is one of the definations of Riemann Zeta function
http://mathworld.wolfram.com/RiemannZetaFunction.html
Problem Loading...
Note Loading...
Set Loading...
We begin by rearranging: ∫ 0 ∞ e x − 1 x 3 d x = ∫ 0 ∞ x 3 1 − 1 / e x 1 / e x d x . Now write 1 − 1 / e x 1 / e x = n = 1 ∑ ∞ ( e x 1 ) n = n = 1 ∑ ∞ e x n 1 which follows directly from the infinite summation formula of geometric series, to get ∫ 0 ∞ x 3 1 − 1 / e x 1 / e x d x = ∫ 0 ∞ x 3 n = 1 ∑ ∞ e x n 1 d x = n = 1 ∑ ∞ ∫ 0 ∞ e x n x 3 d x . We substitute z = x n so that d z = n d x . Putting these yields n = 1 ∑ ∞ ∫ 0 ∞ e x n x 3 d x = n = 1 ∑ ∞ ∫ 0 ∞ e z z 3 n 4 1 d z = ( n = 1 ∑ ∞ n 4 1 ) ( ∫ 0 ∞ e z z 3 d z ) . By the definitions of Gamma and Zeta functions, it now easily follows that ( n = 1 ∑ ∞ n 4 1 ) ( ∫ 0 ∞ e z z 3 d z ) = ζ ( 4 ) Γ ( 4 ) = 9 0 π 4 × 3 ! = 1 5 π 4 which is approximately 6 . 5 . Notice that x 3 can be replaced by x k and the same proof above yields ζ ( k + 1 ) Γ ( k + 1 ) .